Content Creator Community Center Di Pekanbaru Dengan Prinsip Desain Renzo Piano - Agustian, M. Aldi; Aldy, Pedia; Firzal, Yohannes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Content Creator Community Center in Pekanbaru is a place of all activities in the digital and social media fields for content creators. The existence of the Content Creator Community Center in Pekanbaru is supported development of the current digital era and people's interest in digital content, this is reinforced by the formation of a community of creators and the development of a business start-up through digital media in Pekanbaru. Content Creator Community Center has the main function as a means of community, production, and social activities as a meeting place. This studies uses the Renzo Piano design principle which creates a building that has aspects of the interaction between the building, nature and its users through the design principles of the Renzo Piano. Through the design concept of Connected buildings demonstrate to three aspects of design with the principles of Renzo Piano so that they can realize the characteristics and functions of the building as a forum for community, production, and social activities. keywords : Pekanbaru, Content Creator Community Center, Renzo Piano